Impact of large-scale social restriction policy on the economy in Depok City, West Java province - Ridwan Ridwan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
A Large-Scale Social Restrictions (PSBB) are restrictions on certain activities of residents in an area suspected of contracting disease and/or polluted in such a way as to prevent the possibility of spreading disease or pollution. The President of the Republic of Indonesia, Joko Widodo announced the establishment of PSBB as a decision taken by the government in responding to the Health Emergency due to the Coronavirus Disease 2019 (COVID-19) pandemic. The purpose of this study is to describe the economic impact of the implementation of PSBB policies, especially in Depok City, which is carried out as an effort to overcome COVID-19. This research was conducted with a qualitative approach with descriptive-analytical methods.  Activities in data analysis are data reduction, data presentation, and conclusion drawing or verification. The results of this study show that the implementation of PSBB has a significant impact on the economic sector in Depok City, including the tourism, MSME and employment sectors. The impact of the pandemic on the tourism sector due to the closure of tourist destinations. In addition, the impact of PSBB is a decrease in people's income which has an impact on decreasing purchasing power. The strategy carried out by the government to overcome the impact of the implementation of this PSBB is through social assistance programs and the right to a social safety net for the community. So the government needs to consider the impact and risk that will be received by the target group. The government also needs to prepare solutions in case of unwanted negative impacts.